2015
DOI: 10.1007/s10803-015-2422-9
|View full text |Cite
|
Sign up to set email alerts
|

Changing College Students’ Conceptions of Autism: An Online Training to Increase Knowledge and Decrease Stigma

Abstract: College students with autism may be negatively impacted by lack of understanding about autism on college campuses. Thus, we developed an online training to improve knowledge and decrease stigma associated with autism among college students. Participants (N = 365) completed a pre-test, online training, and post-test. Women reported lower stigma towards autism than men. Participation in the training was associated with decreased stigma and increased knowledge about autism. Although participants exhibited relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
268
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 266 publications
(303 citation statements)
references
References 52 publications
24
268
3
8
Order By: Relevance
“…Although the current study may be the first to compare knowledge and stigma associated with ASD across countries, incomplete and/or inaccurate knowledge about ASD has been documented among many types of people internationally, including college students in Great Britain (Shah 2001), Nigeria (Igwe et al 2010), and the US (Tipton and Blacher 2014). Commonly reported misconceptions include underestimating the prevalence of ASD (Dillenburger et al 2013), lack of knowledge about core diagnostic characteristics (Bakare et al 2009;Gillespie-Lynch et al 2015;Heidgerken et al 2005;Helps et al 1999;Kharti et al 2011), misconceptions about etiology (Alqahtani 2012), and insufficient knowledge about how to support those on the spectrum (Chown 2010;Imran et al 2011). Researchers have often found that women and those who have had more contact with people with ASD are more knowledgeable about autism (Dillenburger et al 2013;Koyama et al 2008;Wang et al 2012).…”
Section: Misconceptions About Asd: a Global Phenomenonmentioning
confidence: 96%
See 4 more Smart Citations
“…Although the current study may be the first to compare knowledge and stigma associated with ASD across countries, incomplete and/or inaccurate knowledge about ASD has been documented among many types of people internationally, including college students in Great Britain (Shah 2001), Nigeria (Igwe et al 2010), and the US (Tipton and Blacher 2014). Commonly reported misconceptions include underestimating the prevalence of ASD (Dillenburger et al 2013), lack of knowledge about core diagnostic characteristics (Bakare et al 2009;Gillespie-Lynch et al 2015;Heidgerken et al 2005;Helps et al 1999;Kharti et al 2011), misconceptions about etiology (Alqahtani 2012), and insufficient knowledge about how to support those on the spectrum (Chown 2010;Imran et al 2011). Researchers have often found that women and those who have had more contact with people with ASD are more knowledgeable about autism (Dillenburger et al 2013;Koyama et al 2008;Wang et al 2012).…”
Section: Misconceptions About Asd: a Global Phenomenonmentioning
confidence: 96%
“…To address this need, Gillespie-Lynch et al (2015) used a pre-test post-test design to evaluate an online ASD training. Mirroring Tipton and Blacher's (2014) findings, 365 US college students indicated more correct than incorrect answers on the Autism Awareness Survey at pre-test.…”
Section: Conceptions Of Asd In the Usmentioning
confidence: 99%
See 3 more Smart Citations